RETRO-MACHO LENSING: A WAY TO FIND BLACK HOLE - Syauqin Nadhil, Rafa
The existence of black holes in our universe always creates interesting discussions. However, they are difficult to detect and can only be deciphered using some combination of certain principles in astrophysics. Thus far we have identified two classes of black holes characterized by their masses: stellar mass black holes and supermassive black holes. In the meantime, there is a wide gap between the two classes of black hole: intermediate mass black hole (IMBH). There are indications of their existence, but we need independent methods to confirm their masses. We study a special case of gravitational lensing configuration where light trajectory is deflected and turned around resulting in an image in the sky that can be seen by an observer located between the lens and the light source. This is called Retro-MACHO lensing. In this final project research, we estimated the effect of variation of mass, distance from observer to lens, and misalignment angle to lensing observable apparent magnitude in several cases of black hole’s location with mass range of intermediate mass black hole. Those cases are: black hole in Heliosphere, Oort cloud, and in range between farther of Oort cloud and in the same distance as Proxima Centauri. We found that the most visible and significant effect of three cases came from the variation of mass as it makes a difference of 5 in magnitudes for every 10 times mass difference. The variation of distance between observer and lens will be more significant if the range is bigger. We also found that the image with misalignment around 0 will be much brighter rather than big misalignment. But, the magnitude difference between large misalignment angles is not so significant. Observations of Retro-MACHO is yet to be done, but with the results we got it’s still possible to observe it with the technology we have now for the cases that we worked on with some conditions. With the issue of selection effect, and we know intermediate mass black hole has its own preference of location. So, for our cases, straggler black holes nearby our solar system must mostly consist of stellar mass black holes. But with the results that we got; it is still possible to observe.